Inclusive Education and the Identification of Slow Learners in Mathematics: A Survey Study of Mathematics Teachers' Awareness and Support Needs - Heni Yunilda Hasibuan; Yayat Ruhiat; Cecep Anwar Hadi Firdos Santosa (International Journal of STEM Education for Sustainability, 2025)
Inclusive education has emerged as a critical initiative in promoting equitable learning opportunities for all students, including those with special needs. One of the central challenges in implementing inclusive education lies in identifying and supporting slow learners, particularly in mathematics, where learning difficulties often remain undetected or are misdiagnosed. This study investigates the awareness, experiences and support needs of senior secondary school (SMA/MA/SMK) mathematics teachers in Indonesia regarding inclusive education. The focus of the research is to discover and address the needs of slow learners. A survey was conducted of 173 mathematics teachers from various regions across the country to find out what they know about inclusive education, how they interact with students with special needs, and methods for identifying students who are slow learners in the classroom. The results show that although many teachers understand the importance of inclusive education, formal programs for inclusive education are still limited in many schools. Most teachers can identify various difficulties that students may face. Teachers also say that diagnostic tools are needed to help identify students who are experiencing math difficulties. They emphasized that relying on subjective observations without adequate resources is a very difficult problem. This study shows that the development of specific diagnostic tools is essential to support and identify slow learners early on. In line with Sustainable Development Goal 4 (SDG4), which aims to ensure that all students receive an equitable and inclusive education, regardless of their difficulties, this research supports the broader goal of achieving equitable quality education. To support inclusive education, raising awareness, increasing access to diagnostic tools, and targeted pedagogical support are all important steps. This is especially true for teaching mathematics.